Australia's federal experience - Petchey, Jeffrey Dean; Wells, G. (Routledge, 2004)
In 1901, the former colonies of New South Wales, Victoria, Queensland, Tasmania, Western Australia and South Australia federated to create the nation of Australia under the auspices of a new constitution. Within the federation, the colonies became states and a democratic national parliament with an upper house (the Senate) and a lower house (the House of representatives) was created. The party that achieves a majority of seats in the lower house forms the national government, generally referred to as the Commonwealth.Since then Australia has remained a relatively prosperous democratic federation with two features that distinguish its fiscal arrangements from other federal countries:highly centralized tax powers and a strong emphasis on inter-State equity. Centralization of taxes has its origins in decisions made in the course of framing the Constitution, as well as transfers of taxing powers made during the Second World War. The cornerstone of the emphasis on equity is a federal institution known as the Commonwealth Grants Commission. Created in 1933 following a period of instability in the federal union,the commission implements the most comprehensive system of inter-State transfers of any federal country.The goal of these transfers is to achieve equity across States in the provision of public services.The next two sections of the chapter are organised around two important distinguishing features of Australian federalism-centralization and the emphasis on equity. The conclusion highlights implications of this experience for the European Union.